2022
DOI: 10.3390/insects13040339
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Changes in Metabolite Profiles among Pre-Diapause, Diapause and Post-Diapause Larvae of Sitodiplosis mosellana (Diptera: Cecidomyiidae)

Abstract: Sitodiplosis mosellana, a notorious pest of wheat worldwide, copes with temperature extremes during harsh summers and winters by entering obligatory diapause as larvae. However, the metabolic adaptive mechanism underlying this process is largely unknown. In this study, we performed a comparative metabolomics analysis on S. mosellana larvae at four programmed developmental stages, i.e., pre-diapause, diapause, low temperature quiescence and post-diapause development. In total, we identified 54 differential meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Similar with our results, Li et al (2015) studied the metabonomic characteristics of diapause Aphidius gifuensi and found that the most significantly enriched pathways were also focused on amino acid and carbohydrate metabolism. The result of significantly higher D-glutamine on day 28 might be due to that glutamine accumulated considerably in diapause larvae for their cold tolerance, and similar results has also been found in Sarcophaga crassipalpis and Sitodiplosis mosellana (Michaud and Denlinger, 2007;Huang et al, 2022). Glucose and glutamine also participated in providing nutrients for the metabolism during immune response in insects (Dolezal et al, 2019).…”
Section: Figure 10supporting
confidence: 59%
“…Similar with our results, Li et al (2015) studied the metabonomic characteristics of diapause Aphidius gifuensi and found that the most significantly enriched pathways were also focused on amino acid and carbohydrate metabolism. The result of significantly higher D-glutamine on day 28 might be due to that glutamine accumulated considerably in diapause larvae for their cold tolerance, and similar results has also been found in Sarcophaga crassipalpis and Sitodiplosis mosellana (Michaud and Denlinger, 2007;Huang et al, 2022). Glucose and glutamine also participated in providing nutrients for the metabolism during immune response in insects (Dolezal et al, 2019).…”
Section: Figure 10supporting
confidence: 59%
“…Nevertheless, it has been elucidated for this organic acid to have powerful antimicrobial effect properties against several foodborne pathogens (Ramos et al 2013 ; Salaheen et al 2014 ; Park et al 2016 ). Moreover, biosynthesis of functional metabolites such as fumaric acid is associated with survival and development at extreme high and low temperatures in Diptera such as Sitodiplosis mosellana (Huang et al 2022 ), a process that may be also present during tick developmental and pathogen transmission dynamics (Gray et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…TPS regulates the synthesis of trehalose, the main blood sugar in insects, and it can help insects resist low temperatures and other adverse environments. It has been proven to be involved in regulating diapause in many insects, including the cotton bollworm, Sericinus montelus and Sitodiplosis mosellana [ 51 , 59 , 60 ]. Trehalose is one of the important cold-resistant substances in A. segetum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%